1991
DOI: 10.1161/01.str.22.11.1369
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of new coagulation and fibrinolytic markers in ischemic stroke patients.

Abstract: Background and Purpose:We investigated plasma levels of D-dimer products of crosslinked fibrin degradation products, thrombin-antithrombin III complex, and plasmin-« 2 -antiplasmin complex for detecting coagulation system activation in ischemic stroke patients to determine the possible effect of age on these marker levels.Methods: We measured plasma levels of these three markers in 54 acute ischemic stroke patients within 5 days of stroke onset, in 44 chronic ischemic stroke patients over 3 months from onset, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
5
21
0
Order By: Relevance
“…Moreover, the elevations in FM, TAT-III and D-dimers were so great that they ought primarily to have been due to the effects of coagulation activation and reactive fibri nolysis. Furthermore, these results are in agreement with those of recent studies by Ono et al [12] and Fisher and Francis [13]. Ono et al [12] also showed highly significant differences between a group of 98 stroke patients and a healthy control group as far as the D-dimers and TAT-III complexes were concerned.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the elevations in FM, TAT-III and D-dimers were so great that they ought primarily to have been due to the effects of coagulation activation and reactive fibri nolysis. Furthermore, these results are in agreement with those of recent studies by Ono et al [12] and Fisher and Francis [13]. Ono et al [12] also showed highly significant differences between a group of 98 stroke patients and a healthy control group as far as the D-dimers and TAT-III complexes were concerned.…”
Section: Discussionsupporting
confidence: 92%
“…3, 4), since atherosclero sis is strongly dependent on age. This age-related increase in TAT and other hemostatic marker levels was also found by Ono et al [22], The normal distribution for TAT, Fl+2, and probably for other recently developed markers of hemostatic activity should therefore be cor rected for age.…”
Section: Discussionsupporting
confidence: 81%
“…Ono et al [22] found that the differences of TAT and D-dimer levels between patients and healthy controls increased with age. In our study, even with a limited number of patients, a relationship of TAT and Fl+2 levels and older age ( > 70 years) was also suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulation and fibrinolysis are activated to different degrees in various subtypes of acute ischemic stroke [19, 20, 21, 22, 23, 24]. These differences are ascribed to the different pathogenesis of cardioembolic (CE) and non-cardioembolic (non-CE) ischemic stroke, with more pronounced activation of the coagulation system in CE stroke as compared with atherothrombotic or lacunar strokes [24, 25, 26].…”
Section: Introductionmentioning
confidence: 99%